Biology as destiny? short and long-run determinants of intergenerational transmission of birth weight - Currie, Janet M. 1960-; Moretti, Enrico 1968- (National Bureau of Economic Research, 2005)
"Little is known about the mechanisms underlying the transfer of economic status between generations. This paper addresses the question of whether inter-generational correlations in health contribute to the perpetuation of economic status. We examine inter-generational correlations in birth weight, a key indicator of the health of newborns that we link to future educational attainment and earnings using a unique data set based on California births from 1960s to the present. We use names and birth dates to link the records of mothers and children. We also identify mothers who are siblings. We show that there is a strong intergenerational correlation in the birth weight of mothers and children, but that a measure of household income at the time of the mother's birth is also predictive of low birth weight and that there is an interaction between maternal low birth weight and poverty in the production of low birth weight. Together these findings suggest that intergenerational correlations in health could play a role in the intergenerational transmission of income. Parent's income affects child health, and health at birth affects future income"--National Bureau of Economic Research web site.
Keywords: Birth weight -- Economic aspects -- California; Medical economics